Utilizing collaborative works: an attempt to enhance learners’ participation in English class - Asis Wahyudi; Dian Arsitades Wiranegara; Krisdiana Putra Bagus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This action research project aimed to improve the participation of learners in the class of General English. Collaborative activities were designed by grouping learners to work with the assigned tasks. The data were collected through observation. The findings showed that the participation of learners increased greatly characterized by the involvement of all learners in more active participation through group discussions and presentations of their works. Furthermore, the findings revealed that the learners look more confident to speak, more motivated to complete the assigned tasks, more enjoyable in learning, more focused on the lesson, and more engaged to think critically and creatively. In the attempt to disseminate our teaching experience, this article mainly focuses on the practical implementation of our collaborative action that is aimed to encourage other teachers and practitioners to implement the same research to improve their practices.